2001
DOI: 10.2337/diacare.24.4.619
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term (5-Year) Effects of a Reduced-Fat Diet Intervention in Individuals With Glucose Intolerance

Abstract: OBJECTIVE -To determine whether reducing dietary fat would reduce body weight and improve long-term glycemia in people with glucose intolerance. RESEARCH DESIGN AND METHODS -A 5-year follow-up of a 1-year randomized controlled trial of a reduced-fat ad libitum diet versus a usual diet. Participants with glucose intolerance (2-h blood glucose 7.0 -11.0 mmol/l) were recruited from a Workforce Diabetes Survey. The group that was randomized to a reduced-fat diet participated in monthly smallgroup education session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
140
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(152 citation statements)
references
References 24 publications
(15 reference statements)
6
140
0
4
Order By: Relevance
“…This percentage is higher compared with previous reports of the DPS (Tuomilehto et al, 2001) and the diabetes prevention program (Knowler et al, 2002). On the other hand, our dropout percentage is similar to that of other lifestyle interventions after 1-2 year follow-up (Swinburn et al, 2001;Oldroyd et al, 2006) and to that observed in the DREAM trial after a follow-up for a median of 3 years (Gerstein et al, 2006), with 29.3% (772/2635) dropout in the rosiglitazone group and 25.0% (658/2634) in the CON. Two explanations for the difference between the DPS, diabetes prevention program and SLIM can be given.…”
Section: Dropouts To the Intervention Programmentioning
confidence: 54%
“…This percentage is higher compared with previous reports of the DPS (Tuomilehto et al, 2001) and the diabetes prevention program (Knowler et al, 2002). On the other hand, our dropout percentage is similar to that of other lifestyle interventions after 1-2 year follow-up (Swinburn et al, 2001;Oldroyd et al, 2006) and to that observed in the DREAM trial after a follow-up for a median of 3 years (Gerstein et al, 2006), with 29.3% (772/2635) dropout in the rosiglitazone group and 25.0% (658/2634) in the CON. Two explanations for the difference between the DPS, diabetes prevention program and SLIM can be given.…”
Section: Dropouts To the Intervention Programmentioning
confidence: 54%
“…0 kg/m 2 for intervention group; fasting plasma glucose < 1400 mg/l Design: RCT over 4 years Intervention: intervention group, intensive lifestyle intervention, detailed instructions on lifestyle repeated every 3-4 months during hospital visits; control group, standard intervention Results: after 4 years a significant reduction in risk of DM by 67 . 4%; weight decrease in both groups but significantly greater in the intervention group; subjects with a low insulinogenic index † developed DM at a significantly higher rate than those with a normal index Conclusion: lifestyle intervention designed to achieve and maintain a ideal body weight (BMI < 22 kg/m 2 ) is an effective means of reducing incidence of type 2 DM in men with IGT Japanese male workers (60) n 173, age 35-70 years, workers at high risk for type 2 DM from a centre in Tokyo, Japan Design: RCT with 1 year follow up Aim: to assess the effectiveness of a new dietary education (NDE) programme in reducing plasma glucose levels Intervention: intervention group, NDE through individual counselling by a nutritionist; NDE based on dietary practices by participants, obtained by use of an FFQ; control group, conventional dietary education Results: intervention group had a significantly lower energy intake at dinner daily than the control group; intervention group had a decreased 2 h plasma glucose after 1 year whereas there was an increase in the control group with a significant percentage change Conclusions: the NDE was shown to reduce glucose levels in subjects at high risk for type 2 DM Malmo Feasibility Study (35) 6956 males from Malmo, Sweden, age 47-49 years Design: 5-year screening including an initial 6 months (randomised) pilot study, consisting of dietary treatment and/or increase of PA Intervention: emphasis on lifestyle changes; group A, patients with newly-detected type 2 DM; group B, with IGT, enrolled in the DM prevention programme; group C, non-randomised, not enrolled in the prevention programme, IGT informed their condition; group D, normal control group with normal OGTT Results: BP, lipids and hyperinsulinaemia were reduced; improvement in glucose tolerance was correlated with weight reduction and increased fitness Conclusion: long-term intervention in the form of diet and PA is feasible even on a large scale and substantial metabolic improvement can be achieved that may contribute to prevent or postpone manifest DM Reduced-fat diet (61) 176 participants with glucose intolerance, 2 h blood glucose (7 . 0-11 .…”
Section: Existing Reviews On Interventions For Diabetes Preventionmentioning
confidence: 99%
“…21 This diet emphasizes reducing fat intake, while maintaining adequate levels of micro-and macro-nutrients. Participants in the 1-year program participated in education about reducing dietary fat intake, personal goal setting, selfmonitoring and evaluation through a series of monthly small group meetings with dieticians.…”
Section: Interventionsmentioning
confidence: 99%